2013
DOI: 10.1155/2013/390256
|View full text |Cite
|
Sign up to set email alerts
|

A New Tool to Explore Children’s Social Competencies: The Preschool Competition Questionnaire

Abstract: This paper presents the validation of Preschool Competition Questionnaire (PCQ). The PCQ was completed by the childcare teachers of 780 French-speaking children between the ages of 36 and 71 months. The results of exploratory factor analysis suggest three dimensions involving neither physical nor relational aggression: other-referenced competition, task-oriented competition, and maintenance of dominance hierarchy. The three dimensions are positively correlated with dominance ratings and are linked to social ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 49 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…Cronbach Alpha reliability coefficients of the original scale for each dimension are .89, .75 and .74, respectively. The test-retest reliability coefficient was found as .92, .80 and 69 (p<.001) (Paquette Gagnon, Bouchard, Bigras & Schneider, 2013). The Turkish adaptation of the Preschool Competition Questionnaire (PCQ) was made by Uyanık-Balat, Akman and Arslan Çiftçi in 2017.…”
Section: The Preschool Competition Questionnairementioning
confidence: 99%
See 1 more Smart Citation
“…Cronbach Alpha reliability coefficients of the original scale for each dimension are .89, .75 and .74, respectively. The test-retest reliability coefficient was found as .92, .80 and 69 (p<.001) (Paquette Gagnon, Bouchard, Bigras & Schneider, 2013). The Turkish adaptation of the Preschool Competition Questionnaire (PCQ) was made by Uyanık-Balat, Akman and Arslan Çiftçi in 2017.…”
Section: The Preschool Competition Questionnairementioning
confidence: 99%
“…While some researchers (Sheridan & Williams, 2011) see competition as a detrimental factor to the learning environment, some researchers, on the contrary, have revealed that competition is an important factor that increases learning motivation and motivates learning (Bulut, 2020;Sheridan & Williams, 2011). When the studies conducted in the following years are examined, it has been determined that competition seen in early childhood can be seen in three forms; "other-referenced competition", "taskoriented competition" and "maintenance of dominance hierarchy" (Paquette et al, 2013;Tsiakara & Digelis, 2014). The impact of competition on children is determined by the style and scope of competition in early life.…”
Section: Introductionmentioning
confidence: 99%
“…Schoolchildren who always employ aggression/assertion can be socially isolated, which would prevent them from enjoying the benefits of social life. On the other hand, pupils who only perform cooperation may not defend or assert themselves in the many arising competitive situations (Paquette, Gagnon, Bouchard, Bigras, Schneider, 2013).…”
Section: Prefacementioning
confidence: 99%